Goat farm management and brucella infection among the goats, goat keepers and livestock officers, 2011-2012, Nakhon Si Thammarat Province, Southern Thailand - Thanidtha Te-chaniyom (Prince of Songkla University, 2015)
Thesis (M.Sc. (Epidemiology))--Prince of Songkla University, 2014